Modelo para estimar la capacidad de aporte de nitrogeno del suelo - Benintende, M.C.=700 1 Benintende, M.A.; Sterren, C.; Musante, C.; Saluzzio, M.; De Battista, J.J.
(Es, En)
Ilus., 15 ref.
Keywords: FERTILIDAD DEL SUELO; NITROGENO; DIAGNOSTICO; ABONOS NITROGENADOS; ARGENTINA; AGRISCIENTIA